Growth and Stability Among Complex Societies in Prehistoric Lingnan, Southeast China - Francis Allard (Papers from the Institute of Archaeology, 1997)
One significant advance in the field of Chinese archaeology over past decades has been the identification of numerous prehistoric societies characterized by unequal access to status and wealth (henceforth referred to a 'complex societies') in areas peripheral to the Yellow River valley, a region traditionally regarded as the cradle of Chinese civilization. Lingnan, an area which comprises the two modern provinces of Guangdong and Guanxi in Southeast China, also witnessed the emergence of small-scale complex societies prior to its incorporation into the unified Qin and Han states during the last centuries of the pre-Christian era (Allard 1995). This paper examines the circumstances and features of five instances of complex socio-political development in Lingnan over a period from the late Neolithic to the early Iron Age (ca. 3000-200 B.C.) with each of these trajectories tested against recent models dealing with the issues of societal types, complexity, growth and stability.
Keywords: China, complex societies